Pengaruh konsumsi air kelapa muda (Cocos nucifera L.) dan madu terhadap penurunan mual dan muntah pada ibu hamil trimester I - Citra Hariati, Mayang; Markus Sembiring, Iskandar; Andini Harahap, Febri (Talenta Publisher, 2025)
Nausea and vomiting are common issues experienced by some women during the first trimester of pregnancy. If left untreated, these symptoms may progress into hyperemesis gravidarum, a condition that poses risks to both the mother and the baby. One way to help reduce nausea and vomiting is by consuming coconut water and honey. Young coconut water contains hydrating compounds, and it also provides vitamin B6 (pyridoxine), which has antiemetic effects that can help relieve these symptoms in pregnant women. this study aims to evaluate the effectiveness of young coconut water and honey in lowering the frequency of nausea and vomiting in first trimester pregnant women at the Nurtiana Ginting Clinic. Utilizing a Quasi-Experimental design with a one-group pre-test and post-test format, the research involved 19 pregnant women in their first trimester, selected through purposive sampling based on specific inclusion and exclusion criteria. The PUQE-24 (Pregnancy Unique Quantification of Emesis and Nausea) tool was used to assess symptom frequency before and after the intervention. Statistical analysis using the Wilcoxon test showed a p-value of 0.000 ≤ 0.05, indicating a statistically significant impact of the intervention on reducing nausea and vomiting in early pregnancy. The study concludes that young coconut water and honey are effective in decreasing the frequency of these symptoms. As a result, they are recommended as a non-pharmacological option to help manage and alleviate nausea and vomiting during early pregnancy.